Pengaruh Awareness Bonding Dan Identity Bonding Terhadap Kesetiaan Pelanggan Dealer Salim Jaya Motor Pekalongan Lampung Timur - Febriyanto, Febriyanto; Ratmono, Ratmono; Agita, Agita (Universitas Muhammadiyah Metro, 2023)
From the results of observations made by researchers, it was found that several things wereindicated to cause a lack of customer loyalty, so the researchers conducted a study of thisresearch to determine the purpose of partially or simultaneously the effect of awareness bondingand identity bonding on customer loyalty at the Salim Jaya Motor Dealer, Pekalongan Timur,Lampung. This type of research is quantitative with data collection using a questionnaire asmany as a sample of 96 respondents. The sampling technique used random sampling, while theanalytical tool used was multiple linear regression with partial test decision making (t) andsimultaneous test (f) and the coefficient of determination. The results of the analysis prove thatcustomer loyalty is a deep lasting customer commitment to re-subscribe or re-purchase theselected product/service consistently in the future, even though the influence of the situation andmarketing efforts have the potential to cause behavioral changes, to make it happen, customersneed bonding. So with this Awareness Bonding (X1), Identity Bonding (X2), together have aneffect on Loyalty (Y).